2006
DOI: 10.1074/jbc.m510195200
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Nucleoside Analog R1479 (4′-Azidocytidine) Is a Potent Inhibitor of NS5B-dependent RNA Synthesis and Hepatitis C Virus Replication in Cell Culture

Abstract: Hepatitis C virus (HCV) polymerase activity is essential for HCV replication. Targeted screening of nucleoside analogs identified R1479 (4-azidocytidine) as a specific inhibitor of HCV replication in the HCV subgenomic replicon system (IC 50 ‫؍‬ 1.28 M) with similar potency compared with 2-C-methylcytidine (IC 50 ‫؍‬ 1.13 M). R1479 showed no effect on cell viability or proliferation of HCV replicon or Huh-7 cells at concentrations up to 2 mM. HCV replicon RNA could be fully cleared from replicon cells after pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
180
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(188 citation statements)
references
References 25 publications
6
180
0
Order By: Relevance
“…Drug susceptibility studies and selection experiments with the replicon system have shown that a single mutation, i.e., S282T, confers reduced susceptibility to 2Ј-C-Me-adenosine. The S282T mutation confers cross-resistance to other 2Ј-C-Me nucleotides (18,24). Modeling studies and enzyme kinetic analysis suggested that this mutation can affect binding 1 to 7, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Drug susceptibility studies and selection experiments with the replicon system have shown that a single mutation, i.e., S282T, confers reduced susceptibility to 2Ј-C-Me-adenosine. The S282T mutation confers cross-resistance to other 2Ј-C-Me nucleotides (18,24). Modeling studies and enzyme kinetic analysis suggested that this mutation can affect binding 1 to 7, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…HCV Replicon Assays-HCV replicon assays were performed using either the 2209-23 cell line or the transient replicon system in cured Huh-7 cells as described (6,19). Nucleoside analogs were synthesized at Medivir, dissolved in Me 2 SO, and then diluted in Dulbecco's modified Eagle's medium with 5% (v/v) fetal bovine serum before addition to cells.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA template was predicted to form a single stemloop with an unpaired 3-nucleotide sequence at the 3Ј-end. The nucleotide incorporation reactions and RNA product separation on denaturing polyacrylamide gel were conducted as described (6), except that the reactions were carried out with 0.25 M GG primer and nucleotide triphosphates at the indicated concentrations for 30 min. The kinetics of the single nucleotide incorporation of CTP and CTP analogs were determined with the same RNA oligonucleotide template and primer pair for 25 min at the following assay conditions: 7.5 M 19-nucleotide RNA template, 10 M unlabeled GG primer, 0.075 M 5Ј-end-labeled GG primer, 3 M NS5B, and serial dilutions of CTP or each CTP analog.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations